2010
DOI: 10.2903/j.efsa.2010.1556
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on African Swine Fever

Abstract: The risk that African Swine Fever virus (ASFV) remains endemic in the Trans Caucasian Countries (TCC) and the Russian Federation (RF) is moderate, while the risk of its spread in these regions is high. The resulting risk of introduction from these regions into the EU is moderate most likely through food waste. The risk of ASFV remaining endemic in wild boar and the consequent introduction into the EU was considered low in the TCC and moderate in the RF, mainly due to the higher population density in the RF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 78 publications
(69 reference statements)
0
39
0
2
Order By: Relevance
“…Illegal pork trade and the use of food waste in the animals feeding are recognized the most significant anthropogenic factors of the ASFV dissemination [20][21][22]. Moreover, a large number of private farms with their low bi-osafety level poses additional risks of the disease occurrence and dissemination Previously, Spanish researchers showed that ASFV could persist for several weeks or months in the frozen [23], freshly prepared or raw, as well as salted dried meat [24,25], which was in line with our findings When extrapolating our findings on natural and agricultural objects, it should be focused on the need to observe basic sanitary rules, given the fact that the virus can remain virulent for more than 2 weeks under favorable environment. Among violations, control over which is not often covered by the scope of the Veterinary Services competence and is not appropriately regulated, are i) untimely garbage collection in the recreation areas for citizens or the lack of decent household waste storage places, ii) the spontaneous waste landfill deposits arising along roads, in the outskirts of human settlements or in forest areas, iii) feeding domestic pigs with food waste not subjected to a heat pre-treatment, iv) illegal utilization and storage of slaughterhouse wastes.…”
Section: Titers Of African Swine Fever Virus (Lg Haumentioning
confidence: 99%
“…Illegal pork trade and the use of food waste in the animals feeding are recognized the most significant anthropogenic factors of the ASFV dissemination [20][21][22]. Moreover, a large number of private farms with their low bi-osafety level poses additional risks of the disease occurrence and dissemination Previously, Spanish researchers showed that ASFV could persist for several weeks or months in the frozen [23], freshly prepared or raw, as well as salted dried meat [24,25], which was in line with our findings When extrapolating our findings on natural and agricultural objects, it should be focused on the need to observe basic sanitary rules, given the fact that the virus can remain virulent for more than 2 weeks under favorable environment. Among violations, control over which is not often covered by the scope of the Veterinary Services competence and is not appropriately regulated, are i) untimely garbage collection in the recreation areas for citizens or the lack of decent household waste storage places, ii) the spontaneous waste landfill deposits arising along roads, in the outskirts of human settlements or in forest areas, iii) feeding domestic pigs with food waste not subjected to a heat pre-treatment, iv) illegal utilization and storage of slaughterhouse wastes.…”
Section: Titers Of African Swine Fever Virus (Lg Haumentioning
confidence: 99%
“…To address the first ToR, an update was provided on the ASF situation in the eastern neighbouring countries of the EU since the last Scientific Opinion on African swine fever of the EFSA Panel on Animal health and Welfare (EFSA AHAW Panel, 2010a). To do so, an extensive literature review was carried out, describing the geographic distribution of ASFV, the epidemiological features of the outbreaks and challenges for ASFV prevention and control in the eastern neighbouring countries of the EU.…”
Section: Discussionmentioning
confidence: 99%
“…In January 2014, ASF was again detected and confirmed in Ukraine both in wild boar and domestic pigs and in the Lithuanian population of wild boar (OIE, 2014). In 2009 the European Commission requested a Scientific Opinion on African Swine Fever from EFSA on the risk of endemicity of ASF in the in Trans Caucasian Countries and the Russian Federation, and the risk for the introduction of the virus into the EU from these eastern neighbouring countries (EFSA AHAW Panel, 2010a). In that same period, a Scientific Opinion on the Role of Tick Vectors in the Epidemiology of Crimean-Congo Hemorrhagic Fever and African Swine Fever in Eurasia was adopted, which provided the status on the current state of knowledge the role of the tick vectors in the epidemiology of African swine fever (EFSA AHAW Panel, 2010b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the correlation between the wild boar density and the possible presence and duration of other infectious diseases, such as Aujeszky"s disease, classical swine fever, foot and mouth disease, porcine circovirus type 2 and tuberculosis, has been described (Vicente et al, 2004(Vicente et al, , 2007Rossi et al, 2005;Gortázar et al, 2006;Acevedo et al, 2007;EFSA AHAW Panel, 2010;Boadella et al, 2012).…”
Section: Interpretation Of Tor 2 Andmentioning
confidence: 99%